2015
DOI: 10.1186/s13065-015-0107-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, anticholinesterase and antioxidant potentials of ketoesters derivatives of succinimides: a possible role in the management of Alzheimer’s

Abstract: BackgroundBased on the pharmacological potency and structural features of succinimides, this study was designed to synthesize new ketoesters derivatives of succinimides. Furthermore, the synthesized compounds were evaluated for their possible anticholinesterase and antioxidant potentials. The compounds were synthesized by organocatalytic Michael additions of α-ketoesters to N-aryl maleimides. Acetyl and butyrylcholinesterase inhibitory activities were determined using Ellman’s spectrophotometric assay. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 31 publications
3
72
0
Order By: Relevance
“…The antimicrobial agents may interrupt the synthesis of metabolites which are necessary for the basic integrity of microbes including bacteria and fungi [55, 56]. However, the main problem with the use of antimicrobial and other drugs is the hazardous and toxic effects associated with their use [57, 58]. Secondly, many microbes develop resistance to a specific group of drugs and they become less susceptible to that specific drug [55].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial agents may interrupt the synthesis of metabolites which are necessary for the basic integrity of microbes including bacteria and fungi [55, 56]. However, the main problem with the use of antimicrobial and other drugs is the hazardous and toxic effects associated with their use [57, 58]. Secondly, many microbes develop resistance to a specific group of drugs and they become less susceptible to that specific drug [55].…”
Section: Discussionmentioning
confidence: 99%
“…Major symptoms associated with AD are memory loss, behavioral turbulence and mood disturbance in routine life (Kumar et al, 1998). Several biochemical pathways are followed for the management of AD but one of the most established approach is the inhibition of acetylcholinesterase (AChE) (Zeb et al, 2014; Ahmad et al, 2015; Kamal et al, 2015; Sadiq et al, 2015). The AChE is found in excitable tissues in most erythrocytes and in the placental tissues while butyrylcholinesterase (BChE) is present in nervous system, liver and plasma (Massoulié et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Several cholinesterase inhibitors from natural and synthetic sources are available like galantamine, donepezil, rivastigmine, and tacrine (Schulz, 2003). Numerous researchers have also shown that oxidative stress is an early pathogenic event in AD (Sadiq et al, 2015). Therefore, they supplement their anticholinesterase with antioxidants as free radicals scavengers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACh hydrolyzes to produce choline and acetyl group through the biocatalyst acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) in the synaptic region [1]. Inhibition of AChE enzyme can sustain the ACh depletion, which is the main strategy for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%